Risk factors and coronary angiographic profile in young STEMI patients: results from a tertiary care centre in south-central India - Golla, Abhishek; Kadloor, Parvaiz; Gurrala, Rajashekar R.; Hussain, Kazi Jawwad; Sivadayal, Kolli; Rao, K. Laxman; Hidayathulla, Mohammed; Shaikani, Shabbik Ali (International Journal of Research in Medical Sciences, 2021)
Background: Compared to older counterparts, a significant distinction has been found related to risk factors, clinical presentation, and prognosis of ST-segment elevation myocardial infarction (STEMI) in younger patients. To date, a lack of studies has been looked, specifically at-risk factors and angiographic profile of STEMI among younger patients; with this in mind, we conducted the present study. Methods: This hospital-based, cross-sectional, open-label study was carried out at Deccan College of Medical Sciences between April 2018 and December 2019. Patients under 40 years with the presentation of STEMI were included. All patients were subjected to electrocardiography, 2D echocardiography, and coronary angiogram. Baseline demographics, risk factors, and procedural characteristics were recorded. Results: Of 51 young STEMI patients, 41 (80.4%) were male and 10 (19.6%) were female. The most common risk factors associated with the development of STEMI in young patients were smoking (58.8%), followed by diabetes (45.1%), and dyslipidaemia (45.1%). Anterior wall MI was the most frequent presentation (84.3%). The left anterior descending artery was the most frequently (62.8%) involved vessel, followed by left circumflex artery (9.8%), and right coronary artery (5.9%). Conclusions: Insights gained from the study can aid in identifying clinical characteristics of STEMI in young patients, which may be beneficial to achieve appropriate and timely management. Further, the young population should be educated as to control modifiable risk factors and smoking cessation to prevent coronary artery disease since they belong to the highly productive group in the community.